2009
DOI: 10.1159/000235642
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Ankle Vascular Index as a Predictor of Cognitive Impairment in Community-Dwelling Elderly People: Four-Year Follow-Up

Abstract: Background/Aim: The relation between markers of generalized atherosclerosis and cognitive impairment in old age is controversial. The aim of the study was to evaluate the cardio-ankle vascular index (CAVI) as a predictor of longitudinal changes in cognitive function in older individuals. Methods: We evaluated the cognitive function in elderly people with high (AS(+)) and low (AS(–)) values of CAVI each year over 4 years. Results: The changes in the Hasegawa Dementia Scale Revised (HDS-R) and the mini-mental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
0
37
1
2
Order By: Relevance
“…It was reported that CAVI increases not only with age but also with arteriosclerotic diseases, such as coronary artery disease, carotid arteriosclerosis, chronic kidney disease, and cerebrovascular disease [20][21][22] . Age was significantly correlated with CAVI (r = 0.68, t value = 6.3, p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CAVI increases not only with age but also with arteriosclerotic diseases, such as coronary artery disease, carotid arteriosclerosis, chronic kidney disease, and cerebrovascular disease [20][21][22] . Age was significantly correlated with CAVI (r = 0.68, t value = 6.3, p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Izuhara et al 25) reported that CAVI is indepen- , Izuhara 25) , Miyoshi 26) , Horinaka 27) [Sairaku 29) ] Intima media thickness of cervical artery Nakamura 24) , Ibata 22) , Takaki 20,28) , Izuhara 25) , Miyoshi 26) , Okura 36) , Sairaku 29) , Horinaka 27) , Hayashi 38) Chronic kidney disease [Mortality rate in patients with hemodialysis] Izuhara 25) , Kobuzono 30) , Takenaka 31) , Nakamura 32) , Ueyama 33) , Satoh-Asahara 36) [Kato 40) ] Cerebral infarction, Dementia Yamamoto 39) Metabolic syndrome Satoh 55) Diabetes mellitus Ibata 22) , Izuhara 25) , Okura 37) Hypertension Kubozono 21) , Okura 37) , Takaki 42) , Kadota 43) Dyslipidemia Takaki 28) Smoking Kubozono 21) , Noike 62) Obstructive sleep apnea syndrome Kumagai 60) dently associated with the severity of coronary atherosclerosis. Recently, Miyoshi et al 26) also supported a correlation between CAVI and coronary atherosclerosis.…”
Section: A Coronary Artery Diseaseunclassified
“…In a four-year follow-up study, Yamamoto et al reported 39) that community-dwelling elderly people with a high CAVI value are at a greater risk of cognitive decline. Preliminary study on the relationship between CAVI and cerebrovascular events has been conducted, but not yet published.…”
Section: Cerebrovascular Events and Dementiamentioning
confidence: 99%
“…8,[19][20][21][22][23][24] Arterial stiffness, as measured by conventional carotidfemoral pulse wave velocity (PWV) measurement, aortic PWV measurement or non-invasive brachial-ankle PWV (baPWV) measurement, is associated with microvascular early atherosclerotic changes and is an independent predictor for cardiovascular events and deaths. [1][2][3]7,13,14,[25][26][27][28][29] Furthermore, baPWV can be used to assess for the presence of SBI and WMHs.…”
mentioning
confidence: 99%